CANCELLATION OF MARRIAGE DUE TO FRAUD RELATED TO DEVIANT SEXUAL ORIENTATION AS REFERRED TO IN THE COMPILATION OF ISLAMIC LAW AND MARRIAGE LAW (DECISION NUMBER 1521/PDT.G/2025/PA.TGRS) - Br Lubis, Putri Giofani; Aprilyana Sembiring, Idha; Maharany Barus, Utary (NOMOI Law Review, 2025)
Marriage is carried out with the aim of building a lasting and harmonious relationship in accordance with applicable laws and religious norms. However, in its development, many marriages have been annulled due to deception by one of the partners regarding their sexual orientation. In principle, Indonesian positive law has regulated the annulment of marriage in Article 27 of the Marriage Law and Article 72 of the Compilation of Islamic Law. An annulment request can be submitted if one of the parties feels confused or has experienced an error regarding the identity of the partner. This research is a normative juridical research with a statutory approach (statute approach), a case approach (case approach) and a conceptual approach (conceptual approach). The results of the study indicate that the judge's consideration of the arguments submitted by the applicant is in accordance with statutory regulations. In the Islamic perspective, an annulment of marriage caused by the inequalities of the partners in fulfilling the requirements and pillars of marriage will be considered invalid; however, a marriage annulled due to deviation remains valid under positive law, according to Article 2 Paragraphs (1) and (2). However, deviation can also be grounds for divorce.